Restart: the last chance for the Indian economy - Sharma, Mihir S. (Gurgaon, 2015)
n Restart, Mihir S. Sharma shows what can and must change in India's policies, its administration and even its attitudes. The answers he provides are not obvious. Nor are they all comforting or conventional. Yet they could, in less time than you can imagine, unleash the creativity of a billion hopeful Indians.
Keywords: Economy